Therapeutic Drug Monitoring in a Patient with Metastatic Renal Cell Carcinoma Who Achieved Long-Term Response to Cabozantinib in Third-Line Treatment: A Case Report - Shinichi Maruyama; Masaru Kato; Masaru Ishida; Tatsuru Hiraga; Hiroshi Kanno (Case Reports in Oncology)
Introduction: Treatment strategies for metastatic renal cell carcinoma (mRCC) have advanced, and its prognosis has improved. However, the progression-free survival of patients with mRCC who have received prior treatment is approximately 8 months, and long-term responses are rare. We applied therapeutic drug monitoring to a case of mRCC in which a long-term response of more than 3 years was achieved after the administration of cabozantinib as third-line treatment. Here, we report the changes in the blood concentration of cabozantinib. Case Presentation: The patient was a 67-year-old man who had received sunitinib as the first-line treatment and nivolumab as the second-line treatment for stage IV mRCC. However, the disease progressed, and cabozantinib (40 mg/day) was initiated. Three months after the initiation of cabozantinib, partial tumor shrinkage was achieved. In the sixth month, the dose was reduced to 20 mg/day because of severe palmar-plantar erythrodysesthesia syndrome and anorexia; however, further tumor shrinkage was achieved. Fifteen months after starting cabozantinib, the trough concentration of cabozantinib was 960 ng/mL. Thereafter, cabozantinib concentration was measured almost every month and was found to fluctuate between 583 and 1,938 ng/mL; tumor shrinkage was maintained even at 39 months. Conclusion: Cabozantinib provided long-term benefits for more than 3 years. We emphasize that the measurement of cabozantinib concentration in the blood may play a supporting role as an indicator of long-term response.